2014
DOI: 10.1074/jbc.m113.514828
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Efflux as a New Strategy for Iron Reduction and Transport in Plants

Abstract: Background: Iron long distance transport in plants is underdocumented. Results: Iron is delivered to embryos as ferric complexes with citrate/malate. An ascorbate-mediated reduction step is further required to acquire iron. Conclusion: Ascorbate plays a key role for the chemical reduction and transport of Fe 2ϩ . Significance: The identification of iron ligands and the transport process is crucial to further understand how iron is distributed within the plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 52 publications
3
130
0
Order By: Relevance
“…Whatever the origin of Fe 2+ , we hypothesize that LPR1-dependent Fe 3+ production in the apoplast initiates Fe redox cycling as a potential source of ROS (Kosman, 2010;Meguro et al, 2007). Effluxed ascorbate may reduce the LPR1 product to redox-active Fe 2+ (Grillet et al, 2014), thereby triggering callose deposition and root cell differentiation. Indeed, LPR1 overexpression causes ectopic Fe 3+ and ROS generation in -Pi ( Figure 5D), and genotype-dependent ROS formation in the apoplast is detectable in Pi-deprived root tips ( Figure 6).…”
Section: Lpr1-dependent Fe Accumulation Controls Callose Deposition Imentioning
confidence: 99%
“…Whatever the origin of Fe 2+ , we hypothesize that LPR1-dependent Fe 3+ production in the apoplast initiates Fe redox cycling as a potential source of ROS (Kosman, 2010;Meguro et al, 2007). Effluxed ascorbate may reduce the LPR1 product to redox-active Fe 2+ (Grillet et al, 2014), thereby triggering callose deposition and root cell differentiation. Indeed, LPR1 overexpression causes ectopic Fe 3+ and ROS generation in -Pi ( Figure 5D), and genotype-dependent ROS formation in the apoplast is detectable in Pi-deprived root tips ( Figure 6).…”
Section: Lpr1-dependent Fe Accumulation Controls Callose Deposition Imentioning
confidence: 99%
“…In this case, Fe is present in the apoplast in form of complexes with citrate and malate (Fe(III) 3 Cit 2 Mal 2 , Fe(III) 3 Cit 3 Mal, Fe(III)Cit 2 ) (Roschzttardtz et al 2011;Grillet et al 2013). Interestingly, Grillet et al (2013) showed that before uptake to embryo, Fe(III) was reduced to Fe(II) not enzymatically by ferric reductase, but chemically by ascorbate. Presence of this ascorbate reduction system was shown in two dicotyledonous plants: Pisum sativum and Arabidopsis thaliana (Grillet et al 2013).…”
Section: Iron Traffickingmentioning
confidence: 99%
“…Interestingly, Grillet et al (2013) showed that before uptake to embryo, Fe(III) was reduced to Fe(II) not enzymatically by ferric reductase, but chemically by ascorbate. Presence of this ascorbate reduction system was shown in two dicotyledonous plants: Pisum sativum and Arabidopsis thaliana (Grillet et al 2013). …”
Section: Iron Traffickingmentioning
confidence: 99%
“…It was found that the efflux of ASC in pea embryos could increase ferric reduction (Grillet et al, 2014). Similarly, the mutant of ascorbate biosynthesis genes in Arabidopsis ( vtc2-4 , vtc5-1 , and vtc5-2 ), was significantly reduced the ferric reduction activity and Fe content in embryos (Grillet et al, 2014). In the mammalian brain, the acquisition of iron in astrocytes was dependent on the efflux of ASC (Lane et al, 2010).…”
Section: Introductionmentioning
confidence: 99%